Searching for the Limits of the Creative Potential of a Cultural Tradition - Rzepnikowska, Iwona (Literatura Ludowa. Journal of Folklore and Popular Culture, 2018)
Rewievs: Сергей Неклюдов, Темы и вариации, Издательство Индрик, Москва 2016.